Education of Teachers from Rural Schools: Notes on some Actions and Programs Developed by Higher Education Federal Schools in Minas Gerais State - Rita Laura Avelino Cavalcante; Júlia Loren dos Santos; José Elenito Teixeira Morais (Universidade Federal do Norte do Tocantins, 2018)
This article presents some actions and programs provided by the higher education federal schools of Minas Gerais state in partnership with the Ministry of Education regarding the training of rural teachers. It is part of the research entitled "Políticas públicas de formação do professor das escolas do campo: uma análise da parceria MEC e as IFES mineiras" [Public policy on the education of rural teachers: an analysis of the partnership between the Ministry of Education and federal institutions of higher education in Minas Gerais]. In terms of methodology, a survey of public documents (laws, public notices, decrees, opinions, ordinances, and pedagogical projects), and private documents (supervisor reports collected through semi-structured interviews) was carried out. The results indicate that courses have been implemented in undergraduate, graduate and regular undergraduate teacher education programs in rural education. They show that there has been an expansion in the provision of teacher education courses, whose implementation has been successful, but has also faced difficulties. However, despite some relative achievements, one cannot affirm that public policy on the education of rural teachers has been consolidated in Minas Gerais state, since these actions have not yet overcome the predominant discontinuity of public policy in recent decades.